1959
DOI: 10.1161/01.cir.19.3.386
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vessel Tone in Maintaining Pulmonary Vascular Resistance in Patients with Mitral Stenosis

Abstract: Changes in pulmonary vascular (arteriolar) resistance were estimated in 58 patients with mitral stenosis following mitral valvotoimny and during exercise. Evidence is presented that changes in "resistance" reflect active changes in the caliber of the vessels due to alteration in their smooth muscle tone, valvotonmy being followed by a decrease in tone and exercise by an increase.I T IS well known that patients with mitral stenosis have medial hypertrophy of the pulmonary arteries, that a muscular media develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1961
1961
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…On this basis, regression of pulmonary hypertension in brisket disease noted in the present study would depend primarily on lowering of left ventricular filling pressure. Again, this would be analogous to the situation that obtains in certain patients with mitral stenosis when the valvular obstruction is relieved surgically (10)(11)(12).…”
Section: Discussionmentioning
confidence: 76%
“…On this basis, regression of pulmonary hypertension in brisket disease noted in the present study would depend primarily on lowering of left ventricular filling pressure. Again, this would be analogous to the situation that obtains in certain patients with mitral stenosis when the valvular obstruction is relieved surgically (10)(11)(12).…”
Section: Discussionmentioning
confidence: 76%
“…In a series of 300 patients, Wood observed severe pre-capillary PH (PVR Ͼ 6 WU) complicating mitral stenosis in 26% of patients. 37 In isolated mitral regurgitation with preserved LVEF, 17% of patients had PA systolic pressure (PASP) Ͼ 70 mm Hg 38 and 76% had PASP Ͼ 30 mm Hg. Schwammenthal et al 39 showed that elevated PAP at rest and during exercise in mitral stenosis is related to a greater extent to net atrioventricular compliance than mitral valve area.…”
Section: Mitral Valve Diseasementioning
confidence: 99%
“…[2] Historically, mitral valve disease has probably been the best-described cause of PH. [34] In the current era, heart failure is recognized as the predominant cause of elevated left-sided filling pressures resulting in PH. [5] Despite the high prevalence of WHO Group 2 PH, the major focus of research on PH over the past decade has been on WHO Group 1 pulmonary arterial hypertension (PAH).…”
mentioning
confidence: 99%